PENINGKATAN MOTIVASI KULIAH UNTUK REMAJA DESA SUNGAI ALAI KECAMATAN TEBO TENGAH - Iri Hamzah; Apdoludin Apdoludin; Rita Zunarti; Khairul Saleh (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2024)
This activity aims to foster an understanding of the urgency of education in the future and foster a spirit of motivation to go to college and not give up on the situation. The low understanding of adolescents about the importance of learning for future success is the main factor in this service. This service is in addition to many community members who experience economic difficulties, especially for their children's educational needs. This service activity took respondents from 45 young men/women from Sungai Alai village. This service is carried out with a descriptive method consisting of planning stages, implementation, and evaluation. The method in this service is through counseling for all male/female adolescents, which begins with distributing questionnaires to all village adolescents and closes with the delivery of material and discussion. This service activity produces and can increase the motivation of college-interest adolescents; this is indicated by the number of participants who are very enthusiastic about following it so that they get enlightenment from the obstacles they have experienced. The results of the service that we have done obtained results of 28, 40% answering strongly agree, 31.17% answering agree, 28.59% answering less agree, and 11.85% answering strongly disagree % with details of 36 statements and 4 answers, namely strongly agree, agree, less agree, and strongly disagree.